2018
DOI: 10.1158/1535-7163.mct-17-0603
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response: A Novel Therapeutic Target for Poor Prognostic BRAF Mutant Colorectal Cancer

Abstract: mutations occur in ∼10% of colorectal cancer cases, are associated with poor survival, and have limited responses to BRAF/MEK inhibition with or without EGFR inhibition. There is an unmet need to understand the biology of poor prognostic MT colorectal cancer. We have used differential gene expression and pathway analyses of untreated stage II and stage IIIMT (discovery set: = 31; validation set: = 26) colorectal cancer, and an siRNA screen to characterize the biology underpinning the MT subgroup with poorest o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…In the presence of severe and irreparable ER stress, the UPR activates the intrinsic apoptosis pathway [27]. Several studies demonstrated that agents targeting ER stress and the UPR had antiproliferative effects in cancer cells [2832], suggesting that affecting ER stress pathways may provide novel strategies for cancer therapy. Our results show that CWP232291 triggers ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of severe and irreparable ER stress, the UPR activates the intrinsic apoptosis pathway [27]. Several studies demonstrated that agents targeting ER stress and the UPR had antiproliferative effects in cancer cells [2832], suggesting that affecting ER stress pathways may provide novel strategies for cancer therapy. Our results show that CWP232291 triggers ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of ERK1/2 in response to calcium oscillations is multifaceted. Although ERK1/2 activity counteracts the damages induced by an acute increase in intracellular calcium [45], in colorectal cancer, the oncogenic activation of BRAF/MEK/ERK1/2 induces a chronic ER stress that promotes cell survival and is associated with tumor progression and poor patient outcome [92]. Under nutrients depletion, another condition inducing ER stress, ERK1/2 is activated by the autocrinely produced IL-4 in prostate, breast, ovarian, head, and neck cancers, and contributes to cell survival by activating the anti-apoptotic proteins survivins [93].…”
Section: Erks Favor the Adaptation To Environmental Stressesmentioning
confidence: 99%
“…On the other hand, we expected that the activation of pro-apoptotic arms of the UPR may lead prostate cancer cells to cell death. To verify our hypothesis we tested a new compounds (ONC201) known to induce an integrated stress response ATF4-and CHOP-dependent in other cancer models and in phase I and II trials [2,30] (Figure 2 and Supplementary figure 1, a). For the first time, we observed an ONC201induced activation of all the arms of the UPR in the first 24hours.…”
Section: Discussionmentioning
confidence: 98%
“…Given that downregulation of CHOP led to cell survival, we hypothesized that the activation of pro-apoptotic arms of the UPR may enhance cell death. To achieve this, we utilized two different compounds (HA15 and ONC201) known to activate the UPR in other models [2,30].…”
Section: Chronic Activation Of the Unfolded Protein Response With Imimentioning
confidence: 99%
See 1 more Smart Citation